TRANSABDOMINAL ULTRASOUND: A POTENTIALLY ACCURATE AND USEFUL TOOL FOR DETECTION OF CHOLEDOCHOLITHIASIS - Zahur, Zainab; Jielani, Asif; Fatima, Tatheer; Ahmad, Aness (Journal of Ayub Medical College Abbottabad, 2019)
Background: Choledocholithiasis denotes to the presence of gallstones within the common bile duct. In patients with Gall stones, the precise incidence and prevalence of choledocholithiasis are not known, but it has been estimated that 5 to 20 percent of patients have choledocholithiasis at the time of cholecystectomy, with the incidence increasing with age. The transabdominal ultrasound examination (US) is the most commonly used modality for symptoms attributable to gallstone disease. US can provide important evidence for presence of stones in CBD. Methods: This was a descriptive cross-sectional validation study which was conducted at PAEC General Hospital, Islamabad from February to July 2015. Patients with suspected choledocholithiasis attending radiology department for ultrasound abdomen were included in the study. Findings for dilatation of common bile duct, intrahepatic biliary channel dilatation and direct visualization of calculus in CBD were noted. Ultrasound findings were compared with subsequent ERCP which was considered gold standard. Results: Diagnostic accuracy of trans abdominal ultrasound in detection of choledocholithiasis came out to be 76.9% with sensitivity of 76.2% and specificity of 81.3%. Conclusion: Ultrasound can be used as an initial and baseline tool for detection of CBD calculi as it is non-invasive, easily available, radiation free and cost effective. Keywords: Choledocholithiasis; Trans abdominal ultrasound; Endoscopic retrograde cholangiopancreatography; diagnostic accuracy